Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a book saying,

$\int \delta(x-x')\psi(x)dx = \psi(x')$ where $\psi(x) = \langle x\lvert\psi\rangle$, so our definition of delta function would be $\langle x'\lvert x\rangle = \delta(x-x')$.

However I could find some documents (example; refer to 3. Position Space) saying,

$$\delta(x'-x'') = \langle x'\lvert x''\rangle$$

which corresponds to $\delta(x-x') = \langle x\lvert x'\rangle$.

So the result should be

$$\delta(x-x') = \langle x\lvert x'\rangle (=) \langle x'\lvert x\rangle \tag{1}$$

I think neither of them is an error, because my book uses the definition many times and I have found many documents explaining as $\delta(x-x') = \langle x\lvert x'\rangle$. Is (1) correct?

share|cite|improve this question
up vote 5 down vote accepted

As DJBunk mentions the delta function is symmetric $$\delta(x)=\delta(-x)$$ so you certainly have $$\delta(x-x')=\delta(x'-x).$$

But you should also know that in general we have $$\langle a | b \rangle = \langle b | a \rangle^* $$ and since in this case the inner product is real, you will also have $$\langle x | x' \rangle = \langle x' | x \rangle .$$ So it doesn't matter which way you write the delta function or the inner product.

share|cite|improve this answer
Keep in mind, though, that the delta-function symmetry only holds in the distributional sense. That is, $\delta(-x) = \delta (x) $ simply and only means that $\int_{-\infty}^\infty f(x)\delta(-x)dx=f(0)=\int_{-\infty}^\infty f(x)\delta(x)dx$, which you can prove by changing variables to $y=-x$. – Emilio Pisanty Aug 31 '12 at 20:46
Thank you everyone. I feel released. – true Sep 1 '12 at 11:07

Either way is fine:

$\delta(x-x')= \langle x| x' \rangle= \delta(x' - x) =\langle x'| x \rangle$.

You can see this either from the fact that in the limiting definition

$\delta (x-x') = \lim_{\sigma \rightarrow \infty} \frac{1}{\sqrt{2 \pi} \sigma} e^{-\frac{(x-x')^2}{2 \sigma^2}}$

is symmetric in $x$ and $x'$

or that either form does the same job under an integral:

$ \int^\infty_{-\infty} dx \delta(x-x') = \int^\infty_{-\infty} dx \delta(x' - x) = 1 $

and as Mistake Ink pointed out:

$ \int^\infty_{-\infty} dx f(x' )\delta(x-x') = \int^\infty_{-\infty} dx f(x' ) \delta(x' - x) = f(x) $

share|cite|improve this answer
You should really put a test function under the integrals e.g. $f(x)$ and then see that they both give $f(x')$ to prove what you are trying to say. – Mistake Ink Aug 31 '12 at 16:28
@MistakeInk - thanks. I updated to reflect this. – DJBunk Aug 31 '12 at 16:43
Thank you, especially for your showing definition. – true Sep 1 '12 at 11:07

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.